2014
DOI: 10.1055/s-0034-1372345
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System HIV Infection in “Less-Drug Regimen” Antiretroviral Therapy Simplification Strategies

Abstract: Less-drug regimens (LDR) refer to combinations of either two antiretroviral drugs or ritonavir-boosted protease inhibitor (PI) monotherapy. They may represent a simplification strategy in patients with persistently suppressed human immunodeficiency virus (HIV) viremia, with the main benefits of reducing drug-related toxicities and costs. Systemic virological efficacy of LDR is slightly lower as compared with combined antiretroviral therapy (cART), but patients with failure do not usually develop drug resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 64 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…LPV/r monotherapy is one of the best known options of tailored therapeutic approaches for patients with persistently suppressed HIV viremia in which fewer than the recommended standard of three antiretrovirals are used [ 4 ]. The primary objective of this study was to measure the effect on HIV patients’ quality of life of simplifying conventional TT with an MT regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPV/r monotherapy is one of the best known options of tailored therapeutic approaches for patients with persistently suppressed HIV viremia in which fewer than the recommended standard of three antiretrovirals are used [ 4 ]. The primary objective of this study was to measure the effect on HIV patients’ quality of life of simplifying conventional TT with an MT regimen.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, the use of simplification regimens [ 4 ], initiated once the patient has become stable and virologically suppressed, has become more attractive. Putative advantages of monotherapy (MT) strategies include decreases in toxicity, antiretroviral interactions, treatment complexity and cost, as well as preserving future treatment options, as the PIVOT study has recently shown [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given these interesting findings, strategies involving the switching and simplification of ART regimens (one or less NRTIs, totaling < 3 drugs) have been extensively explored to mitigate drug-induced toxicity, viral resistance, and adherence interruption 3539 . However, the benefits of simplified ART regimens remain controversial because they may be less effective in suppressing CNS viral loads and improving neurological function 4042 . A long-term three-decade retrospective study using a large cohort of 4992 HIV-positive patients with regimen switching protocols demonstrated that neurocognitive deficits do not necessarily improve in most cases, even if systemic viral suppression is successfully achieved 43 .…”
Section: Molecular and Cellular Pathogenesis Underlying Handmentioning
confidence: 99%
“…Factors contributing to the development of NSE include reduced treatment adherence, drug resistance and component drugs in the ART regime with limited CNS penetration [103][104][105][107][108][109][110]. Fortunately, adjustments in ART, taking into account drug resistance, drug potency and CNS drug penetration, can CSF proteome in HIV infection, page 7 usually halt disease progression and, to variable extent, reverse neurological deficits in many of these individuals [95,96], although for some NSE patients the course can be more complicated with recrudescence [103,105,111].…”
Section: Introductionmentioning
confidence: 99%